Maternal Preference, Mode of Delivery and Associated Factors among Women Who Gave Birth at Public and Private Hospitals in Hawassa City, Southern Ethiopia - Zelalem Tenaw; Zemenu Yohannes Kassa; Getinet Kassahun; Animut Ayenew (Ubiquity Press, 2019)
Introduction: Despite the advances in modern obstetrics care, maternal morbidity and mortality remains a big problem. Proper choice in the mode of delivery is necessary to tackle this problem. The aim of this study was to assess maternal preference, mode of delivery and associated factors among women who gave birth at public and private hospitals in Hawassa city, Southern Ethiopia, 2017. Methods: A hospital based cross sectional study was carried out from January 01-30/2017. A systematic sampling procedure was utilized, and 300 mothers who gave births were included in the study. Data entered to EPI data 3.5.1 and exported to version 20.0 software packages for social science analysis. The presence of association between independent and dependent variables was determined using odds ratio at 95% confidence interval by applying logistic regression model. Results: The prevalence of caesarean section was 49.3% (95% CI: 43.7-55.3). Mothers that have a monthly income above poverty line, having previous pregnancy complications, and current pregnancy problems have higher odds of using the caesarean section mode of delivery. Whereas utilization of partograph lower the odds of caesarean section mode of delivery. Having previous pregnancy complications had higher odds of maternal preference for caesarean section delivery whereas the utilization of partograph lowered the odds of maternal preference for Caesarean section delivery. Conclusion: The prevalence of caesarean section mode of delivery in Hawassa city was high compared with world health organization threshold. Monthly income above poverty line, previous pregnancy complications, Current obstetrics problems are increasing caesarean section delivery, whereas utilization of partograph is decreasing caesarean section delivery. Therefore, utilization of partograph could be lessening unnecessary caesarean section delivery.